Experience of trans-sphenoidal excision of pituitary adenomas in a tertiary care hospital in Pakistan - Maryam Butt; Noor Ul Huda Bhatti; Mahnoor Tariq; Ibtissam Bin Khalid; Shayan Khalid Ghaloo; Irfan Yousaf (Journal of the Pakistan Medical Association, 2025)
Objective: To determine the presentation, indications, management and clinical outcomes of patients who underwent trans-sphenoidal excision of pituitary adenomas in a tertiary care setting. Method: The retrospective, descriptive study was conducted at the Shaukat Khanum Memorial Cancer Hospital, Lahore, Pakistan, and comprised records of patients with pituitary adenoma who underwent trans-sphenoidal excision between July 2005 and September 2022. Data was analysed using STATA 15.1. Results: Of the 50 patients, 25(50%) were males and 25(50%) were females. The overall mean age was 43.16±12 years. In 35(70%) cases, tumours were invading the cavernous sinus and were partially resected, 32(64%) tumours were macroadenoma, and 36(72%) were non-secretory. Of the total, 29(58%) patients were discharged within eight days of surgery. Intraoperative cerebrospinal fluid leak was seen in 4(8%) patients. Postoperative complications included anterior pituitary deficiency 17(34%), posterior pituitary deficiency 13(26%) and panhypopituitarism 3(6%). Postoperatively, vision improved in 23(46%) patients. External radiation therapy was offered to 15(30%) patients, while 5(10%) had gamma knife therapy. Conclusion: Patients with non-functioning pituitary adenomas mostly presented later in life, with large adenomas causing compressive symptoms. Key Words: Pituitary adenoma, Endoscopic surgical procedure, Radiotherapy.